(untitled) (Eurasian Research Bulletin, 2025)
The article examines the role of indirect taxes in the tax system of the Republic of Uzbekistan, reforming the tax system, further improving and increasing the efficiency of the tax mechanism, as well as generally recognized international norms and standards in the field of taxation, and draws conclusions from advanced international experiences. . It defines the main directions of improvement of control mechanisms, the main focus is on policy reforms, technological integration and capacity building in tax authorities.